Impact of intravascular ultrasound on the long‐term clinical outcomes in the treatment of coronary ostial lesions. Issue 2 (27th November 2015) - Patel, Yogesh; Depta, Jeremiah P.; Patel, Jayendrakumar S.; Masrani, Shriti K.; Novak, Eric; Zajarias, Alan; Kurz, Howard I.; Lasala, John M.; Bach, Richard G.; Singh, Jasvindar
Abstract : Objectives: To evaluate the long‐term outcomes of patients with ostial lesions who underwent percutaneous coronary intervention (PCI) with and without the use of intravascular ultrasound (IVUS). Background: A higher rate of adverse cardiac events is associated with PCI of ostial lesions as compared with nonostial disease. Methods: From 7/2002 to 8/2010, 225 patients with 233 coronary ostial lesions underwent PCI with ( n  = 82) and without ( n  = 143) IVUS guidance. Ostial lesions included both native aorto‐ostial or major coronary vessel (left anterior descending, left circumflex, and ramus intermedius) lesions. Clinical outcomes [cardiovascular death, myocardial infarction (MI), and target lesion revascularization (TLR)] at a mean follow‐up of 4.2 ± 2.5 years were compared between patients undergoing PCI of an ostial lesion with and without use of IVUS using univariate and propensity score adjusted analyses. Results: Aorto‐ostial lesions ( n  = 109) comprised 47% of lesions, whereas the remaining lesions (53%) involved major coronary vessels. After propensity score adjustment, IVUS use was associated with lower rates of the composite of cardiovascular death, MI, or TLR (HR 0.54, 95% CI 0.29‐0.99; P  = 0.04), composite MI or TLR (HR 0.39, 95% CI 0.18–0.83; P  = 0.01), and MI (HR 0.31, 95% CI 0.11–0.85; P  = 0.02) as compared with no IVUS. The use of IVUS was also associated with a trend towards a lower rate of TLR (HR 0.42, 95% CI 0.17–1.02; P  = 0.06). Conclusions: PCI of coronary ostial lesions with the use of IVUS was associated with significantly lower rates of adverse cardiac events.© 2015 Wiley Periodicals, Inc.